Futsal as a potential talent development modality for soccer - A quantitative assessment of high-level soccer coach and player perceptions - Yiannaki, C.; Carling, C.; Collins, D. (Science and Medicine in Football, 2018)
A contemporary issue in soccer talent development is the potential use of futsal as a training tool. This paper utilised survey methods to quantitatively assess the perspectives of high-level coaches working in youth player education, and players of futsal and 11-a-side soccer (n = 77). Respondents completed surveys before and following a showcase game between an Under-21 international futsal team competing against a Premier League Under-21 soccer team. Responses were positive about futsal as a training aid and specifically regarding skills transfer from futsal into soccer. The majority of respondents (89.6%) indicated "post-game" that futsal could be useful for soccer talent development. Similarly, 90.9% stated they would consider its integration into their programs. Analysis regarding futsal constraints and the impact specific rules may have on skill acquisition generally reported positive perceptions: 89.6% of participants suggested that pitch size improved skills (strongly agree = 33.8%, agree = 55.8%), 88.3% believed the pass back rule enhanced ball reception skills (strongly agree = 27.3%, agree = 61%), and 89.2% perceived that futsal can help develop "multifunctional" players (strongly agree = 27.3%, agree = 62.3%). Knowledge of constraints and the potential for skill acquisition linked to futsal participation is a first step in aiding soccer coaches to understand potential learning returns from its inclusion in talent development policies and programs.